Winter 1981 Study of Black Undergraduate Students Attending Predominantly White, State-Supported Universities. Preliminary Report - Allen, Walter R.; Michigan Univ., Ann Arbor. Center for Afroamerican and African Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Black undergraduate students' educational characteristics, experiences, and outcomes at six predominantly white, State-supported universities were examined in this study. Data were collected from 695 undergraduates by means of questionnaires. Findings show that black students in the study came from high schools where blacks were in the majority, and entered college with established histories of academic achievement. The majority were doing relatively well academically, although their grades were lower than in high school. Frequent exposure to racial discrimination was reported. Many students characterized general relationships between black students and white faculty and staff as negative. However, personal relationships with white faculty, staff, and students were rated good to excellent. Black students also reported that white faculty had difficulty relating to them and tended to avoid interaction with them outside of class. Most students believed white faculty to be concerned about their success but felt that they sometimes evaluated black academic performance unfairly. Socially, black students were at a severe disadvantage. Even though black organizations sponsored activities, over half the students reported infrequent participation in such activities. Most students were reasonably satisfied with the amount of financial aid they received. Finally, despite obvious problems, black students clearly possessed high perceptions of self. (CMG)
Sponsoring Agency: Rockefeller Foundation, New York, NY.
Sponsoring Agency: Spencer Foundation, Chicago, IL.
Sponsoring Agency: Ford Foundation, New York, NY.
ERIC Note: Part of the National Study of Black College Students.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Keywords: Black Students; College Faculty; College Students; Higher Education; Peer Relationship; Racial Discrimination; Racial Relations; Self Concept; State Universities; Student Adjustment; Student Attitudes; Student Characteristics; Student College Relationship; Student Experience; Student Teacher Relationship; Whites; Reports, Research